The house of the seven gables : an authoritative text, backgrounds and sources, essays in criticism - Hawthorne, Nathaniel, 1804-1864 (Norton critical edition, 1967)
Presents the text of Nathaniel Hawthorne's novel about a family living under the curse of a man who was hanged for witchcraft; and includes background information on the story, and a selection of critical reviews and essays.